2019
DOI: 10.1002/jrs.5714
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a high‐performance thermally shrinkable polystyrene SERS substrate via Au@Ag nanorods self‐assembled to detect pesticide residues

Abstract: This paper reports a “bottom‐up” substrate preparation method using a two‐phase interface self‐assembly technology that combines silver‐coated gold core–shell nanorods with the thermally shrinkable polystyrene (TSP) support material for surface‐enhanced Raman spectroscopy (SERS), that is, TSP‐SERS substrate. The gold nanorods with long absorption wavelength were used as the core, and the silver shells were coated to obtain the core–shell nanostructures with a stronger resonance with the wavelength of the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 51 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…In addition, the significant increase in SERS intensity at the beginning is attributed to a decrease in gap size, providing an opportunity for in situ monitoring of changes in interparticle spacing. Moreover, as shown in Table S3 (Supporting Information), the heating temperature and duration required by our method are significantly lower than those required by comparable methods in the literature, [ 30,31,47,48 ] demonstrating the superiority of this method.…”
Section: Resultsmentioning
confidence: 75%
“…In addition, the significant increase in SERS intensity at the beginning is attributed to a decrease in gap size, providing an opportunity for in situ monitoring of changes in interparticle spacing. Moreover, as shown in Table S3 (Supporting Information), the heating temperature and duration required by our method are significantly lower than those required by comparable methods in the literature, [ 30,31,47,48 ] demonstrating the superiority of this method.…”
Section: Resultsmentioning
confidence: 75%
“…Whereas, the previously reported wrinkled film substrate demonstrated sensing of 4-mercaptobenzoic acid up to 10 −9 M concentration resulting in a maximum enhancement factor of the order of 10 7 . 42 Another report by Zhang, L., et al , demonstrated that using a wrinkled nanoporous gold film polymer substrate enabled the sensing of crystal violet and rhodamine-6-G up to 10 −8 M and 10 −11 M concentrations, respectively, with a highest calculated local enhancement factor of ∼10 9 . 17 Thus, the present Au bead@Ag nanorod based shrink film substrate showed a better LOD of 10 −13 M with BDT as the model analyte.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al [ 49 ] described a rapid determination of trace nitrofurantoin in cosmetics by SERS using a nanoarrayed hydroxyl polystyrene‐based substrate. Zhao et al [ 50 ] described the preparation of a high‐performance thermally shrinkable polystyrene SERS substrate via self‐assembled Au@Ag nanorods to detect pesticide residues. They showed by practical detection of benzimidazole pesticide residues that this method has wide applicability for the detection of pesticides.…”
Section: Surface‐enhanced Raman Spectroscopymentioning
confidence: 99%